Twice Removed: Access to Electronic Serials from the User's Point of View - Howarth, Lynne C.; Stoyanova, Penka (Proceedings of the Annual Conference of CAIS / Actes du congrès annuel de l'ACSI, 2013)
Determining user preferences for data elements requisite to identifying print format serial titles in OPACs/WebPACs assumes an even greater priority when extrapolated to electronic serials where notions of seriality and periodicity cease to have the same meaning as in a physical object-oriented venue. This study utilized focus group methodology to define more user-centred bibliographic. . .